PERENCANAAN PEMANENAN AIR HUJAN TERINTEGRASI GREEN ROOF UNTUK MENGATASI KEKURANGAN RUANG TERBUKA HIJAU - Dede Nasrulloh; Neolaka, Amos; Rochadi, Doddy (LPPM, Universitas Negeri Jakarta, 2020)
The research aims to design integrated green roof rainwater harvesting. The design was underway to provide alternative solutions to open green space in Universitas Negeri Jakarta by-law No. 26 of the year 2007 that was not yet satisfied. The law requires a minimum of 10% of the entire land to become open green space. Therefore, the design was carried out on the roof of one of the buildings in Universitas Negeri Jakarta. The design was done through a bold literature study, identifying the physical and biological characteristics, analyzing potential and constraints on the site, and designing with a retrofitting approach. Based on the calculation of the total area of the roof in Universitas Negeri Jakarta using Google Maps, green roof applications can qualify extents of open green space according to the law. The results of the design consist of three areas on the roof vegetation planted using a tub for producing with a height of 30 cm and 60 cm with the types of plants in the form of groundcover and hedgerows. The roof layer is designed with the media is a mixture of plant organic and inorganic material. Keywords: green roof, open green space, rainwater harvesting